2011
DOI: 10.1159/000323391
|View full text |Cite
|
Sign up to set email alerts
|

Uraemia Progression in Chronic Kidney Disease Stages 3–5 Is Not Constant

Abstract: Introduction: Chronic kidney disease (CKD) is a progressive disease leading to loss of glomerular filtration rate (ΔGFR, measured in ml/min/1.73 m2/year). ΔGFR is usually assumed to be constant, but the hyperfiltration theory suggests that it accelerates in severe uraemia. A retrospective analysis of estimated GFR (eGFR) calculated from the Modification of Diet in Renal Disease equation was performed to evaluate whether ΔGFR is constant or accelerating. Methods: 1,441 patients attending a nephrology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…In these studies, the reported annual eGFR decline for the whole CKD population ranged between 1.5 and 2.1 mL/min/1.73 m 2 , and for patients who initiated dialysis, it ranged between 3.9 and 7.3 mL/min/1.73 m 2 . 15 , 17 , 18 Previous literature is in line with our finding that the mean annual rates of kidney function decline in CKD 3–5 cohorts are much lower than in dialysis-based studies.…”
Section: Discussionsupporting
confidence: 87%
“…In these studies, the reported annual eGFR decline for the whole CKD population ranged between 1.5 and 2.1 mL/min/1.73 m 2 , and for patients who initiated dialysis, it ranged between 3.9 and 7.3 mL/min/1.73 m 2 . 15 , 17 , 18 Previous literature is in line with our finding that the mean annual rates of kidney function decline in CKD 3–5 cohorts are much lower than in dialysis-based studies.…”
Section: Discussionsupporting
confidence: 87%
“…The progression of CKD to ESRD often describes an inexorable path from nephron loss to ESRD, where the rate of loss of function is at first linear over time [15] and then accelerates beginning in late stage III CKD [16, 17]. Further, the slope and uniformity of progression rate may vary greatly for individual patients [18].…”
Section: Limitations Of the New Criteria For Adults And Childrenmentioning
confidence: 99%
“…Declines in eGFR, such as a 30% reduction over 2 years, were reported to be strongly and consistently associated with the risks for ESKD and mortality and have been considered an alternative endpoint for CKD progression [ 9 ]. Although the traditional view of kidney function decline in CKD is a steady linear decline (or slope), albeit at different rates among individuals, recent studies have evaluated the trajectories of decline and have shown they are often not linear [ 10 12 ]. The average overall rate of decline reported in 1441 adult individuals with stage 3–5 CKD was 1.47 mL/min/1.73 m 2 ; however, the rate was faster in individuals with eGFR < 30 mL/min/1.73 m 2 and accelerated in the year before the development of ESKD [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the traditional view of kidney function decline in CKD is a steady linear decline (or slope), albeit at different rates among individuals, recent studies have evaluated the trajectories of decline and have shown they are often not linear [ 10 12 ]. The average overall rate of decline reported in 1441 adult individuals with stage 3–5 CKD was 1.47 mL/min/1.73 m 2 ; however, the rate was faster in individuals with eGFR < 30 mL/min/1.73 m 2 and accelerated in the year before the development of ESKD [ 10 ]. Individuals with steeper trajectories were more likely to have been hospitalized and to receive a diagnosis of AKI during hospitalization [ 12 ].…”
Section: Discussionmentioning
confidence: 99%